Penatalaksanaan Fisioterapi Pada Kasus Low Back Pain Myogenic Di RSUD Sukoharjo - Rizky Nur Permanasari, Wafqi; , Arif Pristianto, SSt.FT.,M.Fis (2015)
Background: Low Back Pain (LBP) myogenic is around lower back pain caused by musculoskeletal disorders or abnormalities in the thoracic vertebra 12 to below the hips. Complaints on LBP can cause pain, lower back muscle spasm that causes muscle imbalances so that the stability of the abdominal muscles and lower back down, lumbar mobility is limited, resulting in decreased functional activity. Objective: To investigate the implementation of physiotherapy in reducing pain, increasing range of motion and increase muscle strength in the case of low back pain (LBP) myogenic using Transcutaneus modalities Electrical Nerve Stimulation (TENS) and core stability exercises. Results: after the therapy 6 times showed pain assessment of pain in motion T1: 5.3 cm to T6: 3.8 cm, silent pain T1: 1.5 cm into T6: 1.4 cm, tenderness T1: 7, 3 cm to T6: 2,1cm, increase range of motion flexi T1: being T6:, extension T1: being T6:, the left lateral flexi T1: being T6:, lateral flexi dextra T1: being a T6: 4.1 cm, increase T1 trunk flexor muscle strength: 3 to T6: 4, extensor T1: 3 to T6: 4. Conclusion: Transcutaneus electrical nerve stimulation (TENS) may reduce local pain in the back and core stability exercises can improve muscle kekuaan so as to boost the range of motion trunk. Keywords: Low Back Pain (LBP) myogenic, Transcutaneus electrical nerve stimulation (TENS) and core stability.